Does Birthplace Diversity Affect Economic Complexity? Cross-Country Evidence - Dany Bahar; Hillel Rapoport; Riccardo Turati (Center for Economic Studies and ifo Institute (CESifo), 2019)
We empirically investigate the relationship between a country's economic complexity and the diversity in the birthplaces of its immigrants. Our cross-country analysis suggests that birthplace diversity is strongly and positively associated with economic complexity. This holds particularly for diversity among highly educated migrants and for countries at intermediate levels of economic complexity. The results are robust to accounting for previous trends in birthplace diversity as well as to using alternatives diversity measures. We address endogeneity concerns by instrumenting diversity through predicted stocks from a pseudo-gravity model as well as from a standard shift-share approach. Finally, we provide evidence suggesting that birthplace diversity boosts economic complexity by increasing the diversification of the host country's export basket.
Keywords: F22; O31; O33; 330; economic complexity; birthplace diversity; immigration; growth